2017
DOI: 10.24006/jilt.2017.15.1.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the displacement effect of exports with gravity trade model: China’s textile and clothing case and OBOR implications

Abstract: This paper employs the gravity model to investigate how the growth of China's textile and clothing (T&C) exports is displacing the exports of other Asian developing countries over the 1990-2015 period. Aggregate analyses were undertaken, and the endogeneity of Chinese exports were accounted by applying instrumental variables with country fixed effects. It was found that there was a negative impact of China's emergence on T&C exports on other Asian developing countries. We further explored whether such displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Among Asian countries, China has been a leading clothing manufacturer and exporter since the nineties [10]. However, rising production costs and labor shortages in China have led many clothing manufacturers to relocate their labor-intensive production facilities from China to other, lower-cost, countries in the region such as Vietnam [11], Bangladesh [12], Cambodia [13], and the Philippines [14].…”
Section: Asia's Clothing Exports Under the Brimentioning
confidence: 99%
“…Among Asian countries, China has been a leading clothing manufacturer and exporter since the nineties [10]. However, rising production costs and labor shortages in China have led many clothing manufacturers to relocate their labor-intensive production facilities from China to other, lower-cost, countries in the region such as Vietnam [11], Bangladesh [12], Cambodia [13], and the Philippines [14].…”
Section: Asia's Clothing Exports Under the Brimentioning
confidence: 99%
“…Of those studies included in Table 1, thirteen studies (e.g. Chan and Au 2007;Au and Chan 2008;Chan et al 2008;Tsang and Au 2008;Au and Chan 2010;Chi and Kilduff 2010;Dijankov et al 2010;Lau and Bilgin 2010;Lau et al 2017) were found to focus on bilateral trade for the textiles and/or clothing sector.…”
Section: The Case Of Textiles and Clothing Sectorsmentioning
confidence: 99%
“…Variables used in T&C studies Chan and Au (2007) GDP, PCGDP, distance, population growth, exchange rate, ASEAN Au an GDP, PDGDP. distance, population growth, exchange rate, labour costs, female, value added, EU, NAFTA Chan et al (2008) GDP, PCGDP, distance, population growth, exchange rate, euro currency, WTO member Tsang and Au (2008) Total production, total consumption, labour cost, distance, NAFTA Au and Chan (2010) GDP, PCGDP, exchange rate, population growth, distance, labour costs, female, EU, NAFTA, Chi and Kilduff (2010) GDP, PCGDP, distance, population, population growth, infrastructure degree, country adjacency, common language, literacy, tariffs, APEC, CBI, NAFTA, WTO Djankov et al (2010) Time, export time, GDP, PCGDP, distance, contiguity, language, colony, landlocked Lau and Bilgin (2010) Import quantity, import price, GDP Lee et al (2014) Apparel supply, apparel demand, apparel import, distance, fashion capital Orkan Özer (2014) GNP, Population, distance, exchange rate, EU, Muslim country Macanas (2015) GDP, population, distance, PCGDP, contiguity, landlocked, island, common language, coloniser, time difference, colony, common religion, AFTA Lau et al (2017) GDP, PCGDP, distance, population, exchange rate, labour costs, female, value added, EU, USA, Chan et al (2018) GDP, PCGDP, distance, population, exchange rate, value added, labour costs, female, LPI…”
Section: Authorsmentioning
confidence: 99%
See 2 more Smart Citations